Evaluation of the Air Navigation Technology Study Program Curriculum Based on KKNI and MBKM at Makassar Aviation Polytechnic - Muthmainnah Jufri; Syahrul; Patahuddin (Indonesian Journal Publisher, 2025)
This study evaluates the implementation of the KKNI (National Qualifications Framework) and MBKM (Comprehensive Skills Framework)-based curriculum in the Air Navigation Technology Study Program at Makassar Aviation Polytechnic, focusing on its impact on graduate retention in the workforce. Using the CIPP (Context, Input, Process, Product) evaluation model, this quantitative study involved 50 respondents, consisting of current students and alumni. Data were collected through questionnaires and documentation. The results indicate that all four aspects—context, input, process, and product—have a positive and significant impact on graduate retention in the workforce. These findings indicate that the KKNI and MBKM-based curriculum increases the relevance of graduate competencies to industry needs, strengthens partnerships between academia and industry, and enhances graduate readiness for the professional workforce. This study concludes that the implementation of the curriculum has a significant impact on graduates' competitiveness and employability skills in the aviation sector.